Grid Interconnection of PV System Using Symmetric and Asymmetric MLI Topology - V S Prasadarao K; V Joshi Manohar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
Generally, PV cell converts sunlight into electricity in the form of dc. Integration of PV system with the existing grid requires dc-ac conversion. This conversion is possible with the help of a dc-ac converter known as an inverter. Among all types of the inverter, multilevel inverters (MLIs) are playing a major role with all their major privileges like High power quality, low distortion, less blocking voltages for switching devices. Conventional multilevel inverter topologies such as diode clamped, flying capacitor and cascaded MLIs are having so many disadvantages. One of the common disadvantage among all the conventional MLIs is the requirement of more number of power electronic components as the level of the output voltage increase. To reduce the power electronic components this paper proposes a multilevel inverter topology in symmetrical and asymmetrical configuration. The proposed MLI uses 12 switches and 19 diodes which are very less compared to conventional MLI topologies for generates nine and thirteen level output voltages. Comparison between presented MLI topology and conventional MLI topologies is presented in this paper. Finally, the proposed MLI whose input is fed from the PV system is integrated into the grid. The proposed concept is validated by using the MATLAB/SIMULINK software and the appropriate results are presented in this paper.